Infectious Diseases of North American Black Bears (Ursus americanus): Viral and Bacterial Pathogens (Part One) - Mitchell, Mark; Zimmerman, Dawn (Wildlife Rehabilitation Bulletin, 2021)
Black bears (Ursus americanus) serve as an important keystone species within an ecosystem, and can also serve as sentinels for environmental health. Wildlife rehabilitators, biologists, and veterinarians working with these animals should familiarize themselves with infectious diseases commonly associated with these ursids. The purpose of this article is to provide a literature review of the common viral and bacterial pathogens associated with black bears.